1975
DOI: 10.1007/bf01839143
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of bitumens in continuous and cyclic deformation

Abstract: Viseoelastie properties of bitumens in eontinuous and eyelie deformationA. I. I s a y e v , V. A. Z o l o t a r e v , and G. V V i n o g r a d o v With 13 figures and 2 tables (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Various following studies [4,5] confirmed the validity of the time-temperature superposition principle for the linear behaviour of asphalts. However, for the non-linear behaviour the situation is not so clear.…”
Section: Time-temperature Superposition Principlesupporting
confidence: 51%
See 3 more Smart Citations
“…Various following studies [4,5] confirmed the validity of the time-temperature superposition principle for the linear behaviour of asphalts. However, for the non-linear behaviour the situation is not so clear.…”
Section: Time-temperature Superposition Principlesupporting
confidence: 51%
“…Various authors [5,8] have shown that this relation holds for asphalts. ii) Recently the relation between transient and dynamic linear viscoelastic functions was studied by De la Taille et al [9].…”
Section: Hscoelastic Behaviour Of Asphaltsmentioning
confidence: 82%
See 2 more Smart Citations